2007
DOI: 10.1210/jc.2006-1631
|View full text |Cite
|
Sign up to set email alerts
|

Association of Total Insulin-Like Growth Factor-I, Insulin-Like Growth Factor Binding Protein-1 (IGFBP-1), and IGFBP-3 Levels with Incident Coronary Events and Ischemic Stroke

Abstract: Circulating levels of total IGF-I or IGFBP-1 were not associated with risk of total coronary events or ischemic stroke among older adults, whereas low IGFBP-3 level was associated with increased risk of incident coronary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 36 publications
6
89
2
Order By: Relevance
“…Circulating concentrations of IGF‐I and IGFBP‐3 have been associated with risk of type 2 diabetes, cardiovascular diseases, cancer, and mortality in epidemiological studies (Juul et al ., 2002; Vasan et al ., 2003; Renehan et al ., 2004; Kaplan et al ., 2007; Friedrich et al ., 2009; Burgers et al ., 2011; Rajpathak et al ., 2012). In animal models, diminished IGF‐I/insulin signaling has been associated with extended lifespans (Ziv & Hu, 2011), although the role of the IGF axis in human longevity remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating concentrations of IGF‐I and IGFBP‐3 have been associated with risk of type 2 diabetes, cardiovascular diseases, cancer, and mortality in epidemiological studies (Juul et al ., 2002; Vasan et al ., 2003; Renehan et al ., 2004; Kaplan et al ., 2007; Friedrich et al ., 2009; Burgers et al ., 2011; Rajpathak et al ., 2012). In animal models, diminished IGF‐I/insulin signaling has been associated with extended lifespans (Ziv & Hu, 2011), although the role of the IGF axis in human longevity remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, the GH/IGF-1 axis declines with age with a large variability between individuals, emphasizing the need for prospective studies. Several such studies have been conducted, particularly among elderly people, showing that low IGF-1 is predictive of all-cause and cardiovascular mortality [2,19]. Recently, a bioassay was devised to specifically measure unbound bioactive IGF-1 and elevated IGF-1 bioactivity was found predictive of extended survival among elderly [6].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I, the main effector peptide of the IGF system and the principal mediator of growth hormone (GH) effects, may influence the development of agerelated cardiovascular diseases (7)(8)(9)(10)(11). A report from the Framingham Heart Study identified low IGF-I as a risk factor for incident congestive heart failure (CHF) in the elderly (7).…”
mentioning
confidence: 99%